A multi-responsive indium-viologen hybrid with ultrafast-response photochromism and electrochromism. Issue 86 (14th October 2021) - Pan, Qiu-Yue; Sun, Meng-En; Zhang, Chong; Li, Lin-Ke; Liu, Hua-Li; Li, Kai-Jie; Li, Hai-Yang; Zang, Shuang-Quan
Abstract : A novel 0D organic–inorganic metal halide hybrid (C13 H16 N2 O2 )2 InCl6 ·Cl (1) has been obtained by integrating the mono-viologen derivative with InCl3 . Abstract : A novel 0D organic–inorganic metal halide hybrid (C13 H16 N2 O2 )2 InCl6 ·Cl (1) has been obtained by integrating the mono-viologen derivative with InCl3 . Compound 1 exhibits reversible and ultrafast UV/sunlight/X-ray induced photochromic properties, as well as excellent electrochromic performance, which is the first example of an indium-based organic–inorganic chromic hybrid.